Battery cell, method for producing the same, battery device, electric device, and energy storage device

CN122338176BActive Publication Date: 2026-10-09ZHEJIANG JINKO ENERGY STORAGE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610795784.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-03
Publication Date
2026-10-09
Estimated Expiration
2046-06-03

AI Technical Summary

Technical Problem

[0002]磷酸铁锂因其橄榄石结构,锂离子扩散系数低,电子导电率差,在高温下又面临SEI膜增厚、阻抗增加的问题

Benefits of technology

本申请中,第二活性材料层(表层)高孔隙率确保电解液快速浸润和锂离子快速传输,解决了浓差极化,尤其适用于高电压平台的LFP体系,第一活性材料层(底层)高导电性、低孔隙率确保了电子快速汇集,减少发热;整体压实密度并未因表层多孔而大幅降低,因为底层依然保持了高密度。通过结构设计实现了功能分区;工艺兼容性高,仅需调整配方和涂布参数,无需购置全新设备,可直接在现有双层涂布产线上进行技改,转化成本低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122338176B_ABST
    Figure CN122338176B_ABST
Patent Text Reader

Abstract

The application relates to the energy storage field and provides a battery monomer, a preparation method of the battery monomer, a battery device, a power utilization device and an energy storage device. The battery monomer comprises: an electric core assembly, the electric core assembly comprises a negative electrode sheet, a diaphragm and a positive electrode sheet which are arranged in a stack; a shell, the electric core assembly is located in the shell; and an electrolyte, the electrolyte is located in the shell; the positive electrode sheet comprises a current collector, a first active material layer and a second active material layer, the first active material layer is coated on the surface of the current collector, the second active material layer is coated on the surface of the first active material layer away from the current collector, and the first active material layer and the second active material layer both have a porous structure. The application realizes functional partitioning through structural design; the process compatibility is high, only the formula and coating parameters need to be adjusted, new equipment does not need to be purchased, technical transformation can be directly carried out on an existing double-layer coating production line, and the conversion cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of energy storage technology, and in particular to a battery cell and its preparation method, a battery device, an electrical device, and an energy storage device. Background Technology

[0002] Due to its olivine structure, lithium iron phosphate has a low lithium-ion diffusion coefficient and poor electronic conductivity. At high temperatures, it also faces the problem of SEI film thickening and increased impedance. Summary of the Invention

[0003] This application provides a battery cell and its preparation method, battery device, power consumption device and energy storage device, which can achieve functional partitioning through structural design at least; it has high process compatibility, only requires adjustment of formula and coating parameters, does not require the purchase of new equipment, and can be directly modified on the existing double-layer coating production line, with low conversion cost.

[0004] In a first aspect, this application provides a battery cell, comprising: A battery cell assembly, the battery cell assembly comprising a negative electrode, a separator and a positive electrode stacked together; The housing, in which the battery cell assembly is located; Electrolyte, wherein the electrolyte is located within the housing; The positive electrode includes a current collector, a first active material layer, and a second active material layer. The first active material layer is coated on the surface of the current collector, and the second active material layer is coated on the surface of the first active material layer away from the current collector. Both the first and second active material layers have a porous structure. The porosity P1 of the first active material layer is less than the porosity P2 of the second active material layer, and / or the average pore size D1 of the first active material layer is less than the average pore size D2 of the second active material layer.

[0005] Optional, P2-P1≥8%.

[0006] Optionally, P1 is 15%~20%, and P2 is 25%~35%.

[0007] Optionally, D1 is 0.1μm to 1μm, and D2 is 1μm to 10μm.

[0008] Optionally, the second active material layer may also include thermally expandable microspheres.

[0009] Optionally, the mass fraction of the thermally expandable microspheres in the second active material layer is 3% to 8%.

[0010] Optionally, the sheet resistance R1 of the first active material layer is lower than the sheet resistance R2 of the second active material layer.

[0011] Secondly, this application provides a method for preparing a battery cell, comprising: A battery cell assembly is obtained, the battery cell assembly comprising a negative electrode, a separator, and a positive electrode stacked together; Obtain the housing and place the battery cell assembly inside the housing; Obtain the electrolyte and inject the electrolyte into the casing; A formation process is performed to obtain battery cells; The positive electrode includes a current collector, a first active material layer, and a second active material layer. The first active material layer is coated on the surface of the current collector, and the second active material layer is coated on the surface of the first active material layer away from the current collector. Both the first and second active material layers have a porous structure. The porosity P1 of the first active material layer is less than the porosity P2 of the second active material layer, and / or the average pore size D1 of the first active material layer is less than the average pore size D2 of the second active material layer.

[0012] Optionally, the first active material layer includes lithium salt particles with a first median particle size, and the second active material layer includes lithium salt particles with a second median particle size, wherein the first median particle size is smaller than the second median particle size.

[0013] Optionally, the lithium salt includes at least one of lithium iron phosphate, lithium manganese iron phosphate, and lithium cobalt oxide.

[0014] Optionally, the first median particle size is 0.1 μm to 1 μm, and the second median particle size is 1.0 μm to 10.0 μm.

[0015] Optionally, the first active material layer further includes a first conductive agent, a first binder, and a solvent.

[0016] Optionally, the first conductive agent includes at least one of conductive carbon black and carbon nanotubes; the first binder includes a first polyvinylidene fluoride; and the solvent includes N-methylpyrrolidone.

[0017] Optionally, the second active material layer may further include a second conductive agent, a second binder, thermally expandable microspheres, and a solvent.

[0018] Optionally, the second conductive agent includes at least one of conductive carbon black and conductive graphite; the second binder includes at least one of second polyvinylidene fluoride and polyoxyethylene.

[0019] Optionally, the molecular weight of the second polyvinylidene fluoride is 600,000 g / mol to 1,000,000 g / mol.

[0020] Optionally, the method for preparing the thermally expandable microspheres includes: Prepare the aqueous phase and oil phase separately; The oil phase is added to the aqueous phase and emulsified under high-speed shearing (8000rpm~12000rpm, 5min~15min) in an ice-water bath to form an oil-in-water emulsion. The oil-in-water emulsion was reacted in an oxygen-free atmosphere at 60°C to 70°C to obtain the thermally expanded microspheres. The method for preparing the aqueous phase includes: Add the dispersant, co-dispersant, osmotic pressure regulator, and aqueous phase polymerization inhibitor to deionized water, stir, and adjust the pH value to 8-10 for later use. The method for preparing the oil phase includes: After mixing the monomers and crosslinking agents, add the foaming agent and initiator, and stir at no more than 10°C until completely dissolved, then set aside.

[0021] Optionally, the polymerizing monomer includes at least one of acrylonitrile, methyl methacrylate, and butyl acrylate; the foaming agent includes at least one of isopentane and n-pentane; the initiator includes benzoyl peroxide; the crosslinking agent includes at least one of divinylbenzene and ethylene glycol dimethacrylate; the dispersant includes at least one of silica gel and magnesium hydroxide; the co-dispersant includes sodium dodecylbenzenesulfonate; the osmotic pressure regulator includes sodium chloride; and the aqueous phase polymerization inhibitor includes sodium nitrite.

[0022] Thirdly, this application provides a battery device, including a battery cell as described above, or a battery cell obtained by the preparation method described above, wherein the battery device includes one or more of a battery module, a battery pack, and an energy storage battery.

[0023] Fourthly, this application provides an electrical device that includes a battery device as described above, the battery device being used to provide electrical energy.

[0024] Fifthly, this application provides an energy storage device, which includes a battery device as described above, the battery device being used to store electrical energy.

[0025] The technical solution provided in this application has at least the following advantages: In this application, the high porosity of the second active material layer (surface layer) ensures rapid electrolyte wetting and lithium-ion transport, resolving concentration polarization. This is particularly suitable for LFP systems with high-voltage platforms. The high conductivity and low porosity of the first active material layer (bottom layer) ensure rapid electron aggregation, reducing heat generation. The overall compaction density is not significantly reduced due to the porosity of the surface layer because the bottom layer maintains a high density. Functional zoning is achieved through structural design. The process is highly compatible, requiring only adjustments to the formulation and coating parameters, without the need to purchase new equipment. It can be directly upgraded on existing double-layer coating production lines, resulting in low conversion costs.

[0026] The battery cells provided in this application can be widely used in battery fields requiring high energy density and long cycle life, including high-end electric vehicle battery systems, portable electronic devices, and large-scale energy storage power stations. The battery cells provided in this application can achieve large-capacity energy storage, comprehensively improving energy density, cycle life, and safety performance. They can meet the needs of long-term energy storage, achieving 4 hours or more of long-term energy storage, for example, in energy storage scenarios of 5 hours, 6 hours, and 8 hours. Long-term energy storage refers to the ability to continuously discharge at rated power for 4 hours or even longer, or to achieve large-scale, low-cost energy storage for several days or months. Attached Figure Description

[0027] One or more embodiments are illustrated by way of example with corresponding pictures in the accompanying drawings. These illustrations do not constitute a limitation on the embodiments. Unless otherwise stated, the pictures in the accompanying drawings do not constitute a limitation on scale. In order to more clearly illustrate the technical solutions in the embodiments of this application or in the conventional technology, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 A flowchart corresponding to the method for preparing a single battery cell provided in the embodiments of this application; Figure 2 This is a schematic diagram of the structure of the battery device provided in the embodiments of this application; Figure 3 for Figure 2 A schematic diagram of its breakdown.

[0029] In the diagram: 100, battery assembly; 10, housing; 20, individual battery cell; 11, first part; 12, second part. Detailed Implementation

[0030] As the background technology shows, the mainstream improvement methods for lithium iron phosphate cathode sheets currently include: nano-coating, carbon coating, and the addition of conductive agents. However, under high-rate fast charging conditions (3C~8C), existing cathode sheets have the following technical defects: 1. Severe polarization in liquid phase transport: After traditional electrode rolling, the surface pores are often over-compacted due to the direct pressure of the rolls, resulting in a porosity far lower than that inside the electrode. The electrolyte cannot quickly wet the surface, causing lithium ions to accumulate on the surface and unable to penetrate deep into the electrode.

[0031] 2. Uneven distribution of conductive network: The conductive agent is randomly distributed during slurry mixing, making it prone to agglomeration. The electron conduction path is long and the ohmic polarization is large near the current collector.

[0032] 3. The contradiction between energy density and rate performance: In order to increase the rate, increasing the conductive agent and porosity will inevitably reduce the compaction density and sacrifice the energy density; 4. Limitations of static structures: Whether it is a single-layer uniform structure or a gradient pore structure, its porosity is fixed, which means that the electrode can only achieve optimal performance in a certain temperature range or at a certain magnification.

[0033] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined. Similarly, "multiple sets" refers to two or more sets (including two sets), and "multiple pieces" refers to two or more pieces (including two pieces).

[0034] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0035] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent three cases: A exists, A and B exist simultaneously, and B exists. In addition, the character " / " in this document generally indicates that the related objects before and after it have an "or" relationship.

[0036] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential," etc., indicating orientation or positional relationships, are based on the orientation or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application. For example, if the device or element in the illustration is inverted, then the element described as "below," "under," "below," or "bottom" of other elements or features will be oriented "above" or "top" of said other elements or features. Therefore, the term "below" may cover both above and below orientation depending on the context in which the term is used, which will be obvious to those skilled in the art. Materials may be oriented in other ways (e.g., rotated 90°, inverted, flipped), and the spatial relative descriptive terms used herein may be interpreted accordingly.

[0037] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.

[0038] In the description of embodiments of this application, the terms "about," "approximately," "roughly," or "about" for a numerical value referring to a specific parameter include the numerical value, and those skilled in the art will understand that the deviation from the numerical value is within the acceptable tolerance of the specific parameter. For example, "about" or "about" for a numerical value may include additional numerical values ​​that are in the range of 90.0% to 110.0% of the numerical value, such as in the range of 95.0% to 105.0%, 97.5% to 102.5%, 99.0% to 101.0%, 99.5% to 100.5%, or 99.9% to 100.1%.

[0039] In the accompanying drawings corresponding to the embodiments of this application, the thickness and / or area of ​​layers, films, panels, regions, etc., are enlarged for better understanding and ease of description. Throughout the specification, the same reference numerals denote the same elements. Furthermore, when describing a component as being "generally" formed on another component, it means that the component is not formed on the entire surface (or front surface) of the other component, nor is it formed on a portion of the edge of the entire surface.

[0040] In the description of embodiments of this application, when a component "includes" another component, other components are not excluded unless otherwise stated, and may be further included. When describing a component (such as a layer, film, region, or substrate) on or on the surface of another component, the component may be "directly" located on the surface of the other component, or there may be an intermediate component between the two components. Conversely, when describing a component on the surface of another component, or a component "directly" on another component, or a component surface on which another component is formed or disposed, it indicates that there is no intermediate component between the two components. For simplicity and clarity, various components may be drawn at any scale. In the drawings, some components may be omitted for simplicity.

[0041] The terminology used in the description of the various embodiments herein is for the purpose of describing particular embodiments only and is not intended to be limiting. As used in the description of the various embodiments and the appended claims, the term "the component" is also intended to include the plural form unless the context clearly indicates otherwise.

[0042] The “components” mentioned above can refer to layers, membranes, regions, parts, plates, or structures, etc.

[0043] The embodiments of this application will now be described in detail with reference to the accompanying drawings. However, those skilled in the art will understand that many technical details have been provided in the embodiments of this application to facilitate a better understanding of the application. However, the technical solutions claimed in this application can be implemented even without these technical details and various variations and modifications based on the following embodiments.

[0044] In a first aspect, this application provides a battery cell, comprising: A battery cell assembly, the battery cell assembly comprising a negative electrode, a separator and a positive electrode stacked together; The housing, in which the battery cell assembly is located; Electrolyte, wherein the electrolyte is located within the housing; The positive electrode includes a current collector, a first active material layer, and a second active material layer. The first active material layer is coated on the surface of the current collector, and the second active material layer is coated on the surface of the first active material layer away from the current collector. Both the first and second active material layers have a porous structure. The porosity P1 of the first active material layer is less than the porosity P2 of the second active material layer, and / or the average pore size D1 of the first active material layer is less than the average pore size D2 of the second active material layer.

[0045] The high porosity of the second active material layer (surface layer) ensures rapid electrolyte wetting and lithium-ion transport, resolving concentration polarization. This is particularly suitable for LFP systems with high-voltage platforms. The high conductivity and low porosity of the first active material layer (bottom layer) ensure rapid electron aggregation, reducing heat generation. The overall compaction density is not significantly reduced due to the porous surface layer because the bottom layer maintains high density. Functional zoning is achieved through structural design. It boasts high process compatibility; only adjustments to the formulation and coating parameters are needed, eliminating the need for new equipment. It can be directly upgraded on existing double-layer coating production lines, resulting in low conversion costs.

[0046] Optional, P2-P1≥8%.

[0047] Optionally, P1 is 15%~20%, and P2 is 25%~35%.

[0048] Optionally, D1 is 0.1μm to 1μm, and D2 is 1μm to 10μm.

[0049] Optionally, the second active material layer may also include thermally expandable microspheres.

[0050] Optionally, the mass fraction of the thermally expandable microspheres in the second active material layer is 3% to 8%.

[0051] Optionally, the sheet resistance R1 of the first active material layer is lower than the sheet resistance R2 of the second active material layer.

[0052] Secondly, this application provides a method for preparing a battery cell, comprising: S1. Obtain a battery cell assembly, the battery cell assembly comprising a negative electrode sheet, a separator and a positive electrode sheet stacked together; S2. Obtain the housing and place the battery cell assembly inside the housing; S3. Obtain the electrolyte and inject the electrolyte into the casing; S4. Perform the formation step to obtain battery cells; The positive electrode includes a current collector, a first active material layer, and a second active material layer. The first active material layer is coated on the surface of the current collector, and the second active material layer is coated on the surface of the first active material layer away from the current collector. Both the first and second active material layers have a porous structure. The porosity P1 of the first active material layer is less than the porosity P2 of the second active material layer, and / or the average pore size D1 of the first active material layer is less than the average pore size D2 of the second active material layer.

[0053] Optionally, the first active material layer includes lithium salt particles with a first median particle size, and the second active material layer includes lithium salt particles with a second median particle size, wherein the first median particle size is smaller than the second median particle size.

[0054] Optionally, the lithium salt includes at least one of lithium iron phosphate, lithium manganese iron phosphate, and lithium cobalt oxide.

[0055] Optionally, the first median particle size is 0.1 μm to 1 μm, and the second median particle size is 1.0 μm to 10.0 μm.

[0056] Optionally, the first active material layer further includes a first conductive agent, a first binder, and a solvent.

[0057] Optionally, the first conductive agent includes at least one of conductive carbon black and carbon nanotubes; the first binder includes a first polyvinylidene fluoride; and the solvent includes N-methylpyrrolidone.

[0058] Optionally, the second active material layer may further include a second conductive agent, a second binder, thermally expandable microspheres, and a solvent.

[0059] The working principle of the thermal expansion microspheres is as follows: At room temperature (<45℃): the thermally expanded microspheres are in a contracted state, which does not interfere with the inherent pore structure of the second active material layer. The electrode relies on the static porosity gradient (25%~35% on the surface and 15%~20% on the bottom layer) to achieve ion / electron transport balance at conventional rates.

[0060] High temperature condition (≥45℃): As the internal temperature of the battery rises (e.g., due to heat generated during fast charging or high ambient temperature), the thermally expanding microspheres in the surface layer reach their trigger temperature, causing the outer shell to soften and the internal foaming agent to vaporize. The microspheres expand in volume by 2 to 5 times. The expanded microspheres compress the surrounding large LFP particles and conductive agents, further increasing the porosity of the second active material layer by 5 to 10 percentage points (reaching 30% to 45%). The increased porosity provides a more unobstructed ion transport channel for the electrolyte, whose viscosity decreases at high temperatures, further reducing the resistance to lithium-ion migration. Since the first active material layer contains little or no thermally expanding microspheres (no additional thermally expanding microspheres are added to the first active material layer; however, thermally expanding microspheres may be present at the interface fusion point due to interface characteristics, thus appearing to contain a small amount of thermally expanding microspheres), the structure remains stable and continues to provide a reliable electron conduction path.

[0061] Cooling recovery: When the temperature drops below the trigger temperature, the thermally expanded microspheres shrink, and the porosity of the second active material layer returns to room temperature, achieving reversible dynamic adjustment.

[0062] Optionally, the second conductive agent includes at least one of conductive carbon black and conductive graphite; the second binder includes at least one of second polyvinylidene fluoride and polyoxyethylene.

[0063] Optionally, the molecular weight of the second polyvinylidene fluoride is 600,000 g / mol to 1,000,000 g / mol.

[0064] Optionally, the method for preparing the thermally expandable microspheres includes: Prepare the aqueous phase and oil phase separately; The oil phase is added to the aqueous phase and emulsified under high-speed shearing conditions (8000 rpm ~ 12000 rpm, 5 min ~ 15 min) in an ice-water bath to form an oil-in-water emulsion. The oil-in-water emulsion was reacted in an oxygen-free atmosphere at 60°C to 70°C to obtain the thermally expanded microspheres. The method for preparing the aqueous phase includes: Add the dispersant, co-dispersant, osmotic pressure regulator, and aqueous phase polymerization inhibitor to deionized water, stir, and adjust the pH value to 8-10 for later use. The method for preparing the oil phase includes: After mixing the monomers and crosslinking agents, add the foaming agent and initiator, and stir at no more than 10°C until completely dissolved, then set aside.

[0065] Optionally, the polymerizing monomer includes at least one of acrylonitrile, methyl methacrylate, and butyl acrylate; the foaming agent includes at least one of isopentane and n-pentane; the initiator includes benzoyl peroxide; the crosslinking agent includes at least one of divinylbenzene and ethylene glycol dimethacrylate; the dispersant includes at least one of silica gel and magnesium hydroxide; the co-dispersant includes sodium dodecylbenzenesulfonate; the osmotic pressure regulator includes sodium chloride; and the aqueous phase polymerization inhibitor includes sodium nitrite.

[0066] Optionally, the assembly of the battery cells in this application is carried out according to conventional processes, including electrode preparation, stacking / winding, encapsulation, electrolyte injection, and formation. The electrolyte injection process is the same as that of conventional liquid electrolytes, and the presence of modified CNC does not affect the fluidity of the electrolyte or the electrolyte injection operation. The battery system can be a lithium-ion battery system with silicon-carbon anode and ternary cathode, or other battery systems such as graphite anode and lithium iron phosphate cathode.

[0067] In this application, the positive current collector can be a metal foil or a composite current collector. For example, the metal foil may include, but is not limited to, aluminum foil. The composite current collector may include a base layer and a metal layer located on at least one surface of the base layer. For example, the base layer may be a polymer material base layer, including but not limited to polypropylene (PP) base layer, polyethylene terephthalate (PET) base layer, polybutylene terephthalate (PBT) base layer, polystyrene (PS) base layer, or polyethylene (PE) base layer. The material of the metal layer may include, but is not limited to, aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, or silver alloy.

[0068] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material. As an example, the negative electrode current collector has two opposing surfaces, and the negative electrode film layer is disposed on either or both of the opposing surfaces of the negative electrode current collector.

[0069] The negative electrode current collector can be a metal foil or a composite current collector. For example, the metal foil may include, but is not limited to, copper foil. The composite current collector may include a base layer and a metal layer located on at least one surface of the base layer. For example, the base layer can be a polymer material, including but not limited to polypropylene (PP) base layer, polyethylene terephthalate (PET) base layer, polybutylene terephthalate (PBT) base layer, polystyrene (PS) base layer, or polyethylene (PE) base layer. The material of the metal layer may include, but is not limited to, copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, or silver alloys.

[0070] The negative electrode active material can be any negative electrode active material known in the art for use in battery cells. As an example, the negative electrode active material can be at least one of the following materials, including but not limited to: graphite, carbon materials, silicon-based materials, tin-based materials, or lithium titanate. Graphite can be artificial graphite or natural graphite. Carbon materials can be soft carbon or hard carbon. Silicon-based materials can be selected from at least one of elemental silicon, silicon oxide, silicon-carbon compounds, silicon-nitrogen compounds, and silicon alloys. Tin-based materials can be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other materials that can be used as negative electrode active materials for battery cells can also be used. These negative electrode active materials can be used alone or in combination of two or more.

[0071] Optionally, the negative electrode film may also include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0072] Optionally, the negative electrode film layer may also include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0073] Optionally, the negative electrode film may also include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0074] The membrane material can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. This application does not impose any particular limitation on the type of membrane; for example, a porous membrane with chemical and mechanical stability can be selected.

[0075] The separator can be a single-layer thin film or a multi-layer composite thin film; there are no particular restrictions. When the separator is a multi-layer composite thin film, the materials of each layer can be the same or different; there are no particular restrictions.

[0076] In some specific examples, the separator may include polypropylene (PP) separators, polyethylene (PE) separators, PP / PE / PP three-layer composite separators, ceramic-coated separators, high-strength polymer separators, or functionalized composite separators. PP and PE separators typically have a thickness of 12μm to 25μm and a porosity of 30% to 50%, exhibiting good mechanical strength and chemical stability. Ceramic-coated separators, with a coating of ceramic materials such as Al2O3, SiO2, and TiO2 (coating thickness 2μm to 5μm) on a polyolefin-based membrane, improve high-temperature resistance (thermal shut-off temperature >160℃) and puncture resistance. High-strength polymer separators (such as polyimide (PI), polyethylene terephthalate (PET), and aramid nanofiber separators) possess excellent mechanical properties and high-temperature resistance. Functionalized composite separators (such as separators containing solid electrolyte coatings or lithiophilic coatings) can further enhance lithium deposition stability.

[0077] Thirdly, this application provides a battery device, such as Figure 2 and Figure 3 As shown, the battery device includes the battery cell as described above, or the battery cell obtained by the preparation method described above, and the battery device includes one or more of the following: battery module, battery pack, and energy storage battery.

[0078] Specifically, the battery device 100 includes a housing 10 and individual battery cells 20, with the individual battery cells 20 housed within the housing 10. The housing 10 provides space for the individual battery cells 20, and the housing 10 can have various structures.

[0079] In some embodiments, the housing 10 may include a first portion 11 and a second portion 12, which overlap each other, and together define a receiving space for accommodating the battery cell 20. The second portion 12 may be a hollow structure with one open end, and the first portion 11 may be a plate-like structure, with the first portion 11 covering the open side of the second portion 12 so that the first portion 11 and the second portion 12 together define the receiving space; alternatively, the first portion 11 and the second portion 12 may both be hollow structures with one open side, with the open side of the first portion 11 covering the open side of the second portion 12. Of course, the housing 10 formed by the first portion 11 and the second portion 12 can be of various shapes, such as a cylinder, a cuboid, etc.

[0080] In the battery device 100, the battery cell 20 can be a single cell or multiple cells. Multiple battery cells 20 can be connected in series, parallel, or a combination thereof. A combination thereof means that multiple battery cells 20 are connected in both series and parallel configurations. Multiple battery cells 20 can be directly connected in series, parallel, or a combination thereof to form a whole, which is then housed within the housing 10. Alternatively, the battery device 100 can also consist of multiple battery cells 20 first connected in series, parallel, or a combination thereof to form battery modules, which are then connected in series, parallel, or a combination thereof to form a whole, which is also housed within the housing 10.

[0081] The battery device 100 may also include other structures, for example, the battery device 100 may also include a busbar for realizing electrical connection between multiple battery cells 20.

[0082] Fourthly, this application provides an electrical device that includes a battery device as described above, the battery device being used to provide electrical energy.

[0083] Electrical devices include, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Among them, electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.

[0084] Fifthly, this application provides an energy storage device, which includes a battery device as described above, the battery device being used to store electrical energy.

[0085] Energy storage devices include, but are not limited to, residential energy storage cabinets, commercial energy storage cabinets, energy storage containers, energy storage racks, energy storage power stations, energy storage battery packs, or portable energy storage systems. Energy storage devices may also include energy management systems (EMS), battery management systems (BMS), and power conversion systems (PCS).

[0086] In the examples and comparative examples, the "parts" mentioned in the raw material ratios refer to parts by weight.

[0087] Example 1 This embodiment provides a method for preparing a single battery cell, including: A battery cell assembly is obtained, which includes a negative electrode, a separator, and a positive electrode stacked together. Obtain the housing and place the battery cell assembly inside the housing; Obtain the electrolyte and inject it into the casing; A formation process is performed to obtain battery cells; The methods for preparing the positive electrode include: Provide aluminum foil current collectors; First active material slurry and second active material slurry were prepared respectively; A double-layer slit extrusion coating die is used. The die shims are adjusted to coat the first active material slurry onto the surface of the aluminum foil current collector to form a first wet film. The thickness of the first wet film is controlled to be 90 μm. Within 0.5 s, the second active material slurry is coated onto the first wet film of the first active material layer to form a second wet film. The thickness of the second wet film is controlled to be 50 μm. The coated aluminum foil current collector was dried in a multi-stage oven to obtain a positive electrode with a first active material layer and a second active material layer. The temperature of the first stage oven was controlled at 90℃ (low temperature) to mainly volatilize the surface solvent, causing the PMMA microspheres on the surface to precipitate and form a framework. The temperature of the second stage oven was set at 122℃ (high temperature) to thoroughly dry the bottom layer and to decompose the PMMA microspheres using high temperature, leaving regular pores on the surface. The temperature of the third stage oven was set at 80℃ (cooling down) to avoid thermal stress. The porosity P1 of the first active material layer was 15%, the average pore size D1 was 0.5μm, and the sheet resistance R1 was 13Ω / cm. 2 The porosity P2 of the second active material layer is 30%, the average pore size P2 is 5 μm, and the sheet resistance R2 is 15 Ω / cm. 2 .

[0088] The preparation method of the first active material slurry includes: Lithium iron phosphate particles (D50 particle size of 0.1μm~1μm), conductive carbon black, CNT, and PVDF were mixed with solvent NMP in a mass ratio of 94:3:2:1, and the solid content was controlled at 55% to obtain the first active material slurry.

[0089] The preparation method of the second active material slurry includes: Lithium iron phosphate particles (D50 particle size of 1.0μm~10.0μm), conductive graphite, PVDF with a molecular weight of 1,000,000 g / mol, PMMA pore-forming agent (i.e. PMMA microspheres), and thermally expandable microspheres were mixed with solvent NMP in a mass ratio of 91:2:2:2:3, with the solid content controlled at 45%, to obtain a second active material slurry. The low solid content is conducive to the formation of pores.

[0090] Methods for preparing thermally expandable microspheres include: Mix 100 parts of polymer monomers (acrylonitrile: 62 parts, methyl methacrylate: 30 parts, butyl acrylate: 8 parts) and 0.5 parts of divinylbenzene, then add 25 parts of isopentane and 1.5 parts of benzoyl peroxide, and stir at no more than 10°C until completely dissolved to obtain an oil phase, keeping the temperature of the oil phase below the boiling point of isopentane. Add 5 parts silica gel, 0.5 parts sodium dodecylbenzenesulfonate, 5 parts sodium chloride and 0.5 parts sodium nitrite to 250 parts deionized water, stir at 4000 rpm to disperse evenly, adjust the pH to 8-10 to obtain the aqueous phase; The oil phase was slowly added to the aqueous phase, and the mixture was sheared and emulsified at a high speed of 10,000 rpm for 10 minutes under ice-water bath conditions to form a stable oil-in-water emulsion with an oil droplet size controlled at 10 μm. The emulsion was transferred to a high-pressure reactor, purged with nitrogen three times, maintained at 0.4 MPa, heated to 65°C, and reacted for 18 hours. After cooling, the silica gel was removed by washing with dilute hydrochloric acid with a pH of 2-3, and then washed with deionized water 3-5 times until neutral. The mixture was then filtered, and the thermally expanded microspheres were collected and dried at over 40°C to constant weight.

[0091] The methods for preparing negative electrode sheets include: Anode raw material ratio: artificial graphite: 92wt%, conductive carbon black SP: 3wt%, CMC: 2%, SBR: 3%, wet stirring is carried out, and the final discharge viscosity is controlled at 4000mPa·s~8000mPa·s; Coating: The above slurry is coated on both sides of a copper foil with a thickness of 6μm~8μm, and the coating surface density is controlled at 110g / m². 2 ~135g / m 2 Then it is dried to remove moisture.

[0092] Commercially available PP / PE diaphragms are available as options.

[0093] Electrolyte preparation methods include: In a glove box, ethylene carbonate (EC), ethyl methyl carbonate, and dimethyl carbonate were prepared into a solvent in a volume ratio of 2:3:5. After cooling to below 10°C, LiPF6 was added at a concentration of 1.0 mol / L and stirred until completely dissolved. Ethylene carbonate was then added at a concentration of 2.0 wt% and stirred for 30 min.

[0094] After assembling the stacked small soft-pack batteries, formation is carried out. The methods of transformation include: First, perform a small-current constant-current pre-charge, specifically charging to 3.0V with a constant current of 0.05C; Then, the film is formed by low-current fast charging, specifically by charging at a constant current of 0.1C to 3.35V; Finally, a constant voltage power supply is applied, with a constant voltage of 3.35V and a cutoff current of 0.02C.

[0095] Example 2 This embodiment provides a method for preparing a single battery cell, which differs from Embodiment 1 in that the method for preparing the positive electrode sheet includes: Provide aluminum foil current collectors; First active material slurry and second active material slurry were prepared respectively; A double-layer slit extrusion coating die is used. The die shims are adjusted to coat the first active material slurry onto the surface of the aluminum foil current collector to form a first wet film. The thickness of the first wet film is controlled to be 80 μm. Within 0.5 s, the second active material slurry is coated onto the first wet film of the first active material layer to form a second wet film. The thickness of the second wet film is controlled to be 60 μm. The coated aluminum foil current collector was dried in a multi-stage oven to obtain a positive electrode with a first active material layer and a second active material layer. The temperature of the first stage oven was controlled at 80℃ (low temperature) to mainly volatilize the surface solvent, causing the PMMA microspheres on the surface to precipitate and form a framework. The temperature of the second stage oven was set at 130℃ (high temperature) to thoroughly dry the bottom layer and to decompose the PMMA microspheres using high temperature, leaving regular pores on the surface. The temperature of the third stage oven was set at 80℃ (cooling down) to avoid thermal stress. The porosity P1 of the first active material layer was 20%, the average pore size D1 was 0.1μm, and the sheet resistance R1 was 14Ω / cm. 2 The porosity P2 of the second active material layer is 35%, the average pore size P2 is 1 μm, and the surface resistivity R2 is 17 Ω / cm. 2 .

[0096] The preparation method of the first active material slurry includes: Lithium iron phosphate particles (D50 particle size of 0.1μm~1μm), conductive carbon black, CNT, and PVDF were mixed with solvent NMP in a mass ratio of 93:3:2:2, and the solid content was controlled at 60% to obtain the first active material slurry.

[0097] The preparation method of the second active material slurry includes: Lithium iron phosphate particles (D50 particle size of 1.0μm~10.0μm), conductive graphite, PVDF with a molecular weight of 600000g / mol, PMMA pore-forming agent (i.e. PMMA microspheres), and thermally expandable microspheres were mixed with solvent NMP in a mass ratio of 90:2:2:2:4, with the solid content controlled at 50%, to obtain a second active material slurry. The low solid content is conducive to the formation of pores.

[0098] Methods for preparing thermally expandable microspheres include: Mix 100 parts of polymer monomers (acrylonitrile: 70 parts, methyl methacrylate: 26 parts, butyl acrylate: 4 parts) and 2 parts of divinylbenzene, then add 35 parts of isopentane and 0.5 parts of benzoyl peroxide, and stir at no more than 10°C until completely dissolved to obtain an oil phase, keeping the temperature of the oil phase below the boiling point of isopentane. Add 10 parts magnesium hydroxide, 0.1 parts sodium dodecylbenzenesulfonate, 15 parts sodium chloride and 0.1 parts sodium nitrite to 300 parts deionized water, stir at 5000 rpm to disperse evenly, adjust the pH value to 8-10 to obtain the aqueous phase; The oil phase was slowly added to the aqueous phase, and high-speed shear emulsification was carried out at 12,000 rpm for 15 min under ice-water bath conditions to form a stable oil-in-water emulsion with oil droplet size controlled at 5 μm. The emulsion was transferred to a high-pressure reactor, purged with nitrogen three times, maintained at 0.3 MPa, heated to 70°C, and reacted for 24 hours. After cooling, the silica gel was removed by washing with dilute hydrochloric acid with a pH of 2-3, and then washed with deionized water 3-5 times until neutral. The mixture was then filtered, and the thermally expanded microspheres were collected and dried at over 40°C to constant weight.

[0099] Example 3 This embodiment provides a method for preparing a single battery cell, which differs from Embodiment 1 in that the method for preparing the positive electrode sheet includes: Provide aluminum foil current collectors; First active material slurry and second active material slurry were prepared respectively; A double-layer slit extrusion coating die is used. The die shims are adjusted to coat the first active material slurry onto the surface of the aluminum foil current collector to form a first wet film. The thickness of the first wet film is controlled to be 100 μm. Within 0.5 s, the second active material slurry is coated onto the first wet film of the first active material layer to form a second wet film. The thickness of the second wet film is controlled to be 60 μm. The coated aluminum foil current collector was dried in a multi-stage oven to obtain a positive electrode with a first active material layer and a second active material layer. The temperature of the first stage oven was controlled at 100℃ (low temperature) to mainly volatilize the surface solvent, causing the PMMA microspheres on the surface to precipitate and form a framework. The temperature of the second stage oven was set at 130℃ (high temperature) to thoroughly dry the bottom layer and to decompose the PMMA microspheres using high temperature, leaving regular pores on the surface. The temperature of the third stage oven was set at 90℃ (cooling down) to avoid thermal stress. The porosity P1 of the first active material layer was 15%, the average pore size D1 was 0.5μm, and the sheet resistance R1 was 15Ω / cm. 2 The porosity P2 of the second active material layer is 25%, the average pore size P2 is 5 μm, and the sheet resistance R2 is 16 Ω / cm. 2 .

[0100] The preparation method of the first active material slurry includes: Lithium iron phosphate particles (D50 particle size of 0.1μm~1μm), conductive carbon black, CNT, and PVDF were mixed with solvent NMP in a mass ratio of 93:3:3:1, and the solid content was controlled at 65% to obtain the first active material slurry.

[0101] The preparation method of the second active material slurry includes: Lithium iron phosphate particles (D50 particle size of 1.0μm~10.0μm), conductive graphite, PVDF, PMMA pore-forming agent (i.e. PMMA microspheres), and thermally expandable microspheres were mixed with solvent NMP in a mass ratio of 86:3:2:1:8, with the solid content controlled at 55%, to obtain a second active material slurry. The low solid content is conducive to the formation of pores.

[0102] Methods for preparing thermally expandable microspheres include: Mix 100 parts of polymer monomers (acrylonitrile: 65 parts, methyl methacrylate: 30 parts, butyl acrylate: 5 parts) and 1 part of divinylbenzene, then add 30 parts of isopentane and 1 part of benzoyl peroxide, and stir at no more than 10°C until completely dissolved to obtain an oil phase, and keep the temperature of the oil phase below the boiling point of isopentane. Add 7 parts silica gel, 0.3 parts sodium dodecylbenzenesulfonate, 10 parts sodium chloride and 0.3 parts sodium nitrite to 300 parts deionized water, stir at 4000 rpm to disperse evenly, adjust the pH value to 8-10 to obtain the aqueous phase; The oil phase was slowly added to the aqueous phase, and the mixture was sheared and emulsified at a high speed of 9000 rpm for 10 min under ice-water bath conditions to form a stable oil-in-water emulsion with the oil droplet size controlled at 10 μm. The emulsion was transferred to a high-pressure reactor, purged with nitrogen three times, maintained at 0.4 MPa, heated to 65°C, and reacted for 20 hours. After cooling, the silica gel was removed by washing with dilute hydrochloric acid with a pH of 2-3, and then washed with deionized water 3-5 times until neutral. The mixture was then filtered, and the thermally expanded microspheres were collected and dried at over 40°C to constant weight.

[0103] Example 4 This embodiment provides a method for preparing a single battery cell, which differs from Embodiment 1 in that the method for preparing the positive electrode sheet includes: Provide aluminum foil current collectors; First active material slurry and second active material slurry were prepared respectively; A double-layer slit extrusion coating die is used. The die shims are adjusted to coat the first active material slurry onto the surface of the aluminum foil current collector to form a first wet film. The thickness of the first wet film is controlled to be 80 μm. Within 0.5 s, the second active material slurry is coated onto the first wet film of the first active material layer to form a second wet film. The thickness of the second wet film is controlled to be 40 μm. The coated aluminum foil current collector was dried in a multi-stage oven to obtain a positive electrode with a first active material layer and a second active material layer. The temperature of the first stage oven was controlled at 90℃ (low temperature) to mainly volatilize the surface solvent, causing the PMMA microspheres on the surface to precipitate and form a framework. The temperature of the second stage oven was set at 125℃ (high temperature) to thoroughly dry the bottom layer and to decompose the PMMA microspheres using high temperature, leaving regular pores on the surface. The temperature of the third stage oven was set at 80℃ (cooling down) to avoid thermal stress. The porosity P1 of the first active material layer was 18%, the average pore size D1 was 0.8μm, and the sheet resistivity R1 was 14Ω / cm. 2 The porosity P2 of the second active material layer is 26%, the average pore size P2 is 6 μm, and the sheet resistance R2 is 17 Ω / cm. 2 .

[0104] The preparation method of the first active material slurry includes: Lithium iron phosphate particles (D50 particle size of 0.1μm~1μm), conductive carbon black, CNT, and PVDF were mixed with solvent NMP in a mass ratio of 93:3:2:2, and the solid content was controlled at 60% to obtain the first active material slurry.

[0105] The preparation method of the second active material slurry includes: Lithium iron phosphate particles (D50 particle size of 1.0μm~10.0μm), conductive graphite, PVDF, PMMA pore-forming agent (i.e. PMMA microspheres), and thermally expandable microspheres were mixed with solvent NMP in a mass ratio of 89:2:2:2:5, with the solid content controlled at 50%, to obtain a second active material slurry. The low solid content is conducive to the formation of pores.

[0106] Methods for preparing thermally expandable microspheres include: Mix 100 parts of polymer monomers (acrylonitrile: 70 parts, methyl methacrylate: 22 parts, butyl acrylate: 8 parts) and 1.5 parts of divinylbenzene, then add 25 parts of isopentane and 0.5 parts of benzoyl peroxide, and stir at no more than 10°C until completely dissolved to obtain an oil phase, keeping the temperature of the oil phase below the boiling point of isopentane. Add 8 parts silica gel, 0.4 parts sodium dodecylbenzenesulfonate, 9 parts sodium chloride and 0.4 parts sodium nitrite to 250 parts deionized water, stir at 5000 rpm to disperse evenly, adjust the pH to 8-10 to obtain the aqueous phase; The oil phase was slowly added to the aqueous phase, and the mixture was sheared and emulsified at a high speed of 11,000 rpm for 15 minutes under ice-water bath conditions to form a stable oil-in-water emulsion with an oil droplet size controlled at 15 μm. The emulsion was transferred to a high-pressure reactor, purged with nitrogen three times, maintained at 0.3 MPa, heated to 60°C, and reacted for 24 hours. After cooling, the silica gel was removed by washing with dilute hydrochloric acid with a pH of 2-3, and then washed with deionized water 3-5 times until neutral. The emulsion was filtered, and the thermally expanded microspheres were collected and dried at over 40°C to constant weight.

[0107] Example 5 This embodiment provides a method for preparing a single battery cell, which differs from Embodiment 1 in that the method for preparing the positive electrode sheet includes: Provide aluminum foil current collectors; First active material slurry and second active material slurry were prepared respectively; A double-layer slit extrusion coating die is used. The die shims are adjusted to coat the first active material slurry onto the surface of the aluminum foil current collector to form a first wet film. The thickness of the first wet film is controlled to be 90 μm. Within 0.5 s, the second active material slurry is coated onto the first wet film of the first active material layer to form a second wet film. The thickness of the second wet film is controlled to be 40 μm. The coated aluminum foil current collector was dried in a multi-stage oven to obtain a positive electrode with a first active material layer and a second active material layer. The temperature of the first stage oven was controlled at 80℃ (low temperature) to mainly volatilize the surface solvent, causing the PMMA microspheres on the surface to precipitate and form a framework. The temperature of the second stage oven was set at 130℃ (high temperature) to thoroughly dry the bottom layer and to decompose the PMMA microspheres using high temperature, leaving regular pores on the surface. The temperature of the third stage oven was set at 90℃ (cooling down) to avoid thermal stress. The porosity P1 of the first active material layer was 20%, the average pore size D1 was 0.5μm, and the sheet resistance R1 was 15Ω / cm. 2 The porosity P2 of the second active material layer is 30%, the average pore size P2 is 5 μm, and the sheet resistance R2 is 18 Ω / cm. 2 .

[0108] The preparation method of the first active material slurry includes: Lithium iron phosphate particles (D50 particle size of 0.1μm~1μm), conductive carbon black, CNT, and PVDF were mixed with solvent NMP in a mass ratio of 92:3:3:2, and the solid content was controlled at 65% to obtain the first active material slurry.

[0109] The preparation method of the second active material slurry includes: Lithium iron phosphate particles (D50 particle size of 1.0μm~10.0μm), conductive graphite, PVDF, PMMA pore-forming agent (i.e. PMMA microspheres), and thermally expandable microspheres were mixed with solvent NMP in a mass ratio of 89:2:2:2:5, with the solid content controlled at 55%, to obtain a second active material slurry. The low solid content is conducive to the formation of pores.

[0110] Methods for preparing thermally expandable microspheres include: Mix 100 parts of polymer monomers (acrylonitrile: 66 parts, methyl methacrylate: 27 parts, butyl acrylate: 7 parts) and 2 parts of divinylbenzene, then add 25 parts of isopentane and 1.5 parts of benzoyl peroxide, and stir at no more than 10°C until completely dissolved to obtain an oil phase, keeping the temperature of the oil phase below the boiling point of isopentane. Add 9 parts magnesium hydroxide, 0.2 parts sodium dodecylbenzenesulfonate, 12 parts sodium chloride and 0.3 parts sodium nitrite to 300 parts deionized water, stir at 4000 rpm to disperse evenly, adjust the pH to 8-10 to obtain the aqueous phase; The oil phase was slowly added to the aqueous phase, and high-speed shear emulsification was carried out at 10,000 rpm for 15 min under ice-water bath conditions to form a stable oil-in-water emulsion with oil droplet size controlled at 15 μm. The emulsion was transferred to a high-pressure reactor, purged with nitrogen three times, maintained at 0.4 MPa, heated to 65°C, and reacted for 18 hours. After cooling, the silica gel was removed by washing with dilute hydrochloric acid with a pH of 2-3, and then washed with deionized water 3-5 times until neutral. The mixture was then filtered, and the thermally expanded microspheres were collected and dried at over 40°C to constant weight.

[0111] Comparative Example 1 The only difference between this comparative example and Example 1 is that P2-P1=5%.

[0112] Comparative Example 2 The only difference between this comparative example and Example 1 is that the second active material layer does not contain thermally expandable microspheres.

[0113] The performance of the battery cells obtained in each embodiment and comparative example was tested (the testing methods were all conventional methods in the art), and the results are shown in Table 1.

[0114] As can be seen from the comparison between Example 1 and Comparative Example 1, when the difference between the porosity P1 of the first active material layer and the porosity P2 of the second active material layer is less than 8%, the first active layer and the second active layer of the electrode are not clearly distinguishable. The porosity of the second active layer is relatively small compared to the example, making it difficult for the electrolyte to penetrate from the surface layer to the lower porosity active material at the bottom layer. Furthermore, the two cannot play a synergistic role, resulting in the degradation of the battery's initial coulombic efficiency, 500-cycle capacity retention, and other performance characteristics.

[0115] As can be seen from the comparison between Example 1 and Comparative Example 2, when the second active material layer does not contain thermally expandable microspheres, it is impossible to increase the porosity of the second active material layer when the internal temperature of the battery rises, which affects the wetting of the electrolyte and will cause the following adverse effects: 1. This leads to increased irreversible lithium consumption and reduced initial cycle efficiency; 2. The inability to form a stable and uniformly thick CEI film, and the lack of sufficient pores to buffer volume changes, results in a decrease in capacity retention over 500 cycles. 3. The inability to increase electron conduction paths leads to reduced energy efficiency at 3C rates and reduced capacity retention at -20℃.

[0116] Table 1

[0117] Those skilled in the art will understand that the above embodiments are specific examples of implementing this application, and in practical applications, various changes in form and detail can be made without departing from the spirit and scope of this application. Any person skilled in the art can make various alterations and modifications without departing from the spirit and scope of this application; therefore, the scope of protection of this application should be determined by the scope defined in the claims.

Claims

1. A battery cell, characterized in that, include: A battery cell assembly, the battery cell assembly comprising a negative electrode, a separator and a positive electrode stacked together; The housing, in which the battery cell assembly is located; Electrolyte, wherein the electrolyte is located within the housing; The positive electrode includes a current collector, a first active material layer, and a second active material layer. The first active material layer is coated on the surface of the current collector, and the second active material layer is coated on the surface of the first active material layer away from the current collector. Both the first and second active material layers have a porous structure. The porosity P1 of the first active material layer is less than the porosity P2 of the second active material layer, and the average pore size D1 of the first active material layer is less than the average pore size D2 of the second active material layer. The second active material layer includes thermally expandable microspheres, which expand when the internal temperature of the battery rises to the trigger temperature and contract when the internal temperature of the battery drops below the trigger temperature, wherein the trigger temperature is 45°C. P2-P1≥8%.

2. The battery cell according to claim 1, characterized in that, P1 is 15%~20%, and P2 is 25%~35%.

3. The battery cell according to claim 1, characterized in that, D1 is 0.1μm~1μm, and D2 is 1μm~10μm.

4. The battery cell according to claim 1, characterized in that, The thermally expandable microspheres have a mass fraction of 3% to 8% in the second active material layer.

5. The battery cell according to claim 1, characterized in that, The sheet resistance R1 of the first active material layer is lower than the sheet resistance R2 of the second active material layer.

6. A method for preparing a single battery cell, characterized in that, include: A battery cell assembly is obtained, the battery cell assembly comprising a negative electrode, a separator, and a positive electrode stacked together; Obtain the housing and place the battery cell assembly inside the housing; Obtain the electrolyte and inject the electrolyte into the casing; A formation process is performed to obtain battery cells; The positive electrode includes a current collector, a first active material layer, and a second active material layer. The first active material layer is coated on the surface of the current collector, and the second active material layer is coated on the surface of the first active material layer away from the current collector. Both the first and second active material layers have a porous structure. The porosity P1 of the first active material layer is less than the porosity P2 of the second active material layer, and / or the average pore size D1 of the first active material layer is less than the average pore size D2 of the second active material layer. The second active material layer includes thermally expandable microspheres, which expand when the internal temperature of the battery rises to the trigger temperature and contract when the internal temperature of the battery drops below the trigger temperature, wherein the trigger temperature is 45°C. P2-P1≥8%.

7. The method for preparing a single battery cell according to claim 6, characterized in that, The first active material layer includes lithium salt particles with a first median particle size, and the second active material layer includes lithium salt particles with a second median particle size, wherein the first median particle size is smaller than the second median particle size.

8. The method for preparing a battery cell according to claim 7, characterized in that, The first median particle size is 0.1 μm to 1 μm, and the second median particle size is 1.0 μm to 10.0 μm.

9. The method for preparing a battery cell according to claim 6 or 7, characterized in that, The first active material layer also includes a first conductive agent, a first binder, and a solvent.

10. The method for preparing a battery cell according to claim 9, characterized in that, The first conductive agent includes at least one of conductive carbon black and carbon nanotubes; the first binder includes a first polyvinylidene fluoride; and the solvent includes N-methylpyrrolidone.

11. The method for preparing a battery cell according to claim 6 or 7, characterized in that, The second active material layer also includes a second conductive agent, a second binder, and a solvent.

12. The method for preparing a battery cell according to claim 11, characterized in that, The second conductive agent includes at least one of conductive carbon black and conductive graphite; the second binder includes at least one of second polyvinylidene fluoride and polyoxyethylene.

13. The method for preparing a battery cell according to claim 11, characterized in that, The method for preparing the thermally expandable microspheres includes: Prepare the aqueous phase and oil phase separately; The oil phase is added to the aqueous phase, and shear emulsification is performed under ice-water bath conditions to form an oil-in-water emulsion. The oil-in-water emulsion was reacted in an oxygen-free atmosphere at 60°C to 70°C to obtain the thermally expanded microspheres. The method for preparing the aqueous phase includes: Add the dispersant, co-dispersant, osmotic pressure regulator, and aqueous phase polymerization inhibitor to deionized water, stir, and adjust the pH value to 8-10 for later use. The method for preparing the oil phase includes: After mixing the monomers and crosslinking agents, add the foaming agent and initiator, and stir at no more than 10°C until completely dissolved, then set aside.

14. The method for preparing a single battery cell according to claim 13, characterized in that, The polymerizing monomer includes at least one of acrylonitrile, methyl methacrylate, and butyl acrylate; the foaming agent includes at least one of isopentane and n-pentane; the initiator includes benzoyl peroxide; the crosslinking agent includes at least one of divinylbenzene and ethylene glycol dimethacrylate; the dispersant includes at least one of silica gel and magnesium hydroxide; the co-dispersant includes sodium dodecylbenzenesulfonate; the osmotic pressure regulator includes sodium chloride; and the aqueous phase polymerization inhibitor includes sodium nitrite.

15. A battery device, characterized in that, The battery device includes a battery cell as described in any one of claims 1 to 5, or a battery cell obtained by the preparation method as described in any one of claims 6 to 14, and the battery device includes one or more of a battery module, a battery pack, and an energy storage battery.

16. An electrical appliance, characterized in that, The electrical device includes the battery device as described in claim 15, the battery device being used to provide electrical energy.

17. An energy storage device, characterized in that, The energy storage device includes the battery device as described in claim 15, the battery device being used to store electrical energy.

Citation Information

Patent Citations

  • Method for improving safety of lithium ion battery

    CN112332030A

  • Thermal expansion microsphere and preparation method thereof

    CN117050374A

  • Positive plate, lithium battery and preparation method thereof

    CN121687847A